Sox7 negatively regulates prostate-specific membrane antigen (PSMA) expression through PSMA-enhancer - Peng, Wei (Prostate, 2018)
BACKGROUND. PSMA expression in the prostate epithelium is controlled by a cis-element, PSMA enhancer (PSME). PSME contains multiple binding sites for Sox proteins, and in this study, we identified Sox7 protein as a negative regulator of PSMA expression through its interaction with PSME. METHODS. The statistical correlation between Sox7 and PSMA mRNA expression was evaluated using five prostate cancer studies from cBioportal. In vitro and in vivo interaction between Sox7 and PSME was evaluated by chromatin immunoprecipitation (ChIP), electrophoretic mobility shift assay (EMSA), and luciferase reporter assay. Synthetic oligonucleotides were generated to define the sites in PSME that interact with Sox7 protein. Sox7 mutants were generated to identify the region of this protein required to regulate PSMA expression. Sox7 was also stably expressed in LNCaP/C4–2 and 22Rv1 cells to validate the regulation of PSMA expression by Sox7 in vivo. RESULTS. Sox7 mRNA expression negatively correlated with PSMA/FOLH1 and PSMAL/FOLH1B mRNA expression in Broad/Cornell, TCGA and MSKCC studies, but not in two studies containing only metastatic prostate tumors. PC-3 cells mostly expressed the 48.5 KDa isoform 2 of Sox7, and the depletion of this isoform did not restore PSMA expression. Ectopic expression of canonical, wild-type Sox7 in C4–2 and 22Rv1 cells suppressed PSMA protein expression. ChIP assay revealed that canonical Sox7 protein preferentially interacts with PSME in vivo, and EMSA identified the SOX box sites #2 and #4 in PSME as required for its interaction. Sox7 was capable of directly binding to PSME and suppressed PSME-mediated transcription. The NLS regions of Sox7, but not its β-catenin interacting motif, are essential for this suppressing activity. Furthermore, restoration of wild-type Sox7 expression but not Sox7-NLS mutant in Sox7-null prostate cancer cell lines suppressed PSMA expression. CONCLUSIONS. The inactivation of canonical Sox7 is responsible for the upregulated expression of PSMA in non-metastatic prostate cancer.